The Cambridge handbook of human dignity : interdisciplinary perspectives - Düwell, Marcus, 1962-; Braarvig, Jens; Brownsword, Roger; Mieth, Dietmar (Cambridge : University press, 2014)
"This introduction to human dignity explores the history of the notion from antiquity to the nineteenth century, and the way in which dignity is conceptualised in non-Western contexts. Building on this, it addresses a range of systematic conceptualisations, considers the theoretical and legal conditions for human dignity as a useful notion and analyses a number of philosophical and conceptual approaches to dignity. Finally, the book introduces current debates, paying particular attention to the legal implementation, human rights, justice and conflicts, medicine and bioethics, and provides an explicit systematic framework for discussing human dignity. Adopting a wide range of perspectives and taking into account numerous cultures and contexts, this handbook is a valuable resource for students, scholars and professionals working in philosophy, law, history and theology"--
"Human Dignity was established in 1948 as the foundational concept of the Universal Declaration of Human Rights (UDHR). The Preamble to the Declaration opens with the statement: 'Whereas recognition of the inherent dignity and of the equal and inalienable rights of all members of the human family is the foundation of freedom, justice and peace in the world....' In Article 1, we read: 'All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood.' And, in 1966, the United Nations declared: 'These [human] rights derive from the inherent dignity of the human person' . During the preparation of the Declaration (1946-1948) , there were discussions about whether there was a need for such a foundational concept and, if so, which notion that should be. Choosing human dignity immediately after the war was a statement against the Shoah, against totalitarianism, and against the atrocities of World War II. However, by choosing Human Dignity, a concept was selected that has an impressive history in various traditions. The stoic philosopher Cicero saw it as a central requirement of a virtuous life that one should behave in a way that is appropriate to the dignity of a human being; and, famously, for Immanuel Kant, the dignity of the human person is at the centre of his moral philosophy"--
Machine generated contents note: Introduction: 1. Human dignity from a legal perspective; 2. Human dignity - concept, discussions, philosophical perspectives; Part I. Origins of the Concept in European History: 3. Meritocratic and civic dignity in Greco-Roman antiquity; 4. Human dignity in the Middle Ages, twelfth to fourteenth century; 5. Human dignity in late-medieval spiritual and political conflicts; 6. The Council of Valladolid, 1550-1551: a European disputation about the human dignity of indigenous peoples of the Americas; 7. Human dignity in the Renaissance; 8. Martin Luther's conception of human dignity; 9. Natural rights vs. human dignity: two conflicting traditions; 10. Human dignity in Rousseau and the French Revolution; 11. Human dignity and socialism; 12. Human dignity in the Jewish tradition; Part II. Beyond the Scope of the European Tradition: 13. The concepts of human dignity in moral philosophies of indigenous peoples of the Americas; 14. Human dignity in the Islamic world; 15. Hinduism: the universal self in a class society; 16. Buddhism: inner dignity and absolute altruism; 17. Human dignity in traditional Chinese Confucianism; 18. Dignity in traditional Chinese Daoism; Part III. Systematic Conceptualization: 19. Social and cultural presuppositions for the use of the concept of human dignity; 20. Is human dignity the ground of human rights?; 21. Human dignity - can a historical foundation alone suffice?; 22. Kantian perspectives on the rational basis of human dignity; 23. Kantian dignity: a critique; 24. Human dignity and human rights in Alan Gewirth's moral philosophy; 25. Human dignity in the capability approach; 26. Human dignity in Catholic thought; 27. Jacques Maritain's personalist conception of human dignity; 28. Scheler and human dignity; 29. Dignity and the Other: dignity and the phenomenological tradition; 30. Dignity, fragility, singularity in Paul Ricoeur's ethics; 31. Human dignity as universal nobility; 32. Dignity in the Ubuntu tradition; 33. Posthuman dignity; 34. Dignity as the right to have rights: human dignity in Hannah Arendt; 35. Individual and collective dignity; Part IV. Legal Implementation: 36. Equal dignity in international human rights; 37. Is human dignity a useless concept? Legal perspectives; 38. Human dignity in French law; 39. Human dignity in German law; 40. Human dignity in US law; 41. Human dignity in South American law; 42. Human dignity in South African law; 43. The Islamic world and the alternative declarations of human rights; 44. The protection of human dignity under Chinese law; 45. Human dignity in Japanese law; 46. The place of dignity in the Indian constitution; Part V. Conflicts and Violence: 47. Human dignity and war; 48. Treatment of prisoners and torture; 49. Human dignity and prostitution; 50. Human dignity, immigration and refugees; Part VI. Contexts of Justice: 51. Human dignity and social welfare; 52. Dignity and global justice; 53. Human dignity and people with disabilities; 54. Human dignity as a concept for the economy; 55. Human dignity and gender inequalities; 56. The rise and fall of freedom of online expression; Part VII. Biology and Bioethics: 57. The threefold challenge of Darwinism to an ethics of human dignity; 58. On the border of life and death: human dignity in bioethics; 59. Human dignity and commodification in bioethics; 60. Dignity only for humans? A controversy; 61. Dignity only for humans? On the dignity and inherent value of non-human beings; 62. Human dignity and future generations.
Bibliografija nakon svakog poglavlja.
Str. 570-608: Kazalo
Keywords: građanski odgoj i obrazovanje; ljudska prava; ljudsko dostojanstvo -- - povijesni pregled -- - filozofski aspekti -- - konceptualni aspekti